Pathogenesis, Early Detection, and Treatment ofKeratoconus:An Updated Narrative Review - Juran, Taylor; Maluli, Isabela Agi; Shaw, Julia; Patel, Lila; Sathyamoorthy, Mohanakrishnan (Annals of Eye Science, 2026)
Background and Objective: Keratoconus (KC) is a progressive corneal ectatic disorder characterized by progressive corneal stromal thinning, irregular steeping, and resultant visual impairment. The disease arises from a multifactorial interplay between genetic, biomechanical, biological, environmental, oxidative stressors, and ocular inflammatory factors. Advances in imaging modalities have allowed for earlier detection of subclinical disease, while emerging extracellular matrix (ECM) biomarkers (e.g. LOX, MMP-9, PCPE) offer promise for improved disease monitoring and prognostication. Additionally, recent integration of artificial intelligence and machine learning technologies with corneal imaging and biological data shows promising enhanced diagnostic precision. Therapeutically, corneal collagen crosslinking (CXL) remains the gold standard for halting disease progression, with novel transepithelial CXL techniques, topography-guided photorefractive keratectomy (PRK), and intracorneal ring implantation continuing to expand treatment options. This review ed to provide a comprehensive updated review of the pathophysiology of keratoconus, to allow continued optimization of individual patient management and improve long term outcomes in KC.Methods: This narrative review was conducted using a literature search in PubMed. Articles were published in English between 2023 and 2025. Emphasis was placed on recent advances in pathophysiology of keratoconus, diagnostics, and management options.Key Content and Findings: Recent literature highlights significant progress in understanding the molecular and structural basis of keratoconus. New imaging technologies – including high-resolution corneal tomography and biomechanical assessment tools – enable earlier and more accurate detection of subclinical keratoconus. The identification of tear-film and stromal biomarkers, including LOX and MMP-9, supports the development of non-invasive diagnostic and prognostic strategies. Additionally, AI-driven models that integrate imaging and molecular data have demonstrated improved sensitivity and specificity in early diagnosis compared to current technologies. From a therapeutic perspective, refinements in CXL protocols, including accelerated and transepithelial techniques, have enhanced safety and patient comfort while maintaining efficacy. Thus, combined approaches offer promising in visual rehabilitation and disease stabilization.Conclusions: Overall, the convergence of genomics, proteomics, and computational modeling highlights the transition toward a future of precision-based, individualized, KC management. Continued integration of these new innovations will help to continue improving early detection, risk stratification, and personal treatment strategies.